Recurrent embryonal testicular carcinoma, clinically healed after seven years - Pollak, Erich W; Mérola, Lorenzo; Möller, Germán (Cirugía del Uruguay, 2020)
A 24 year old patient was operated on for an embryonal carcinoma of the testes, which had undergone repeated local-regional recurrences, treated with relative success by surgical and actinic meanm, followed by subsequent spontaneous, total regression.